Planificación curricular en la práctica docente de acuerdo al modelo de Educación Intercultural bilingüe, del Cecib “Galte yaguachi - Gloria Gladys, Lema Curichumbi (2021)
ABSTRACT How the curricular planning is executed is closely related to the fulfillment of the educational objectives and the expected learning results in the students. In this sense, this work's general goal is to unveil the factors associated with the micro curricula planning process carried out by the teachers of the "Galte Yaguachi" Community Educational Center under the approach of the Bilingual Intercultural Education Model (MOSEIB). The methodological approach of this work is qualitative and is based on the interpretive paradigm. The modality was a field with a descriptive level. The data collection technique was the focus group applied to the teachers of the institution under study. The resulting information was processed through categorization, and inclusive codes and categories were generated based on the responses of the interviewees and the research objectives. The conclusions indicate that the teaching planning does not conform to the MOSEIB guidelines, and a greater process of accompaniment and training is required for the teachers in charge of designing and executing said planning. Keywords: curricular planning, MOSEIB, teachers, educational policy. Reviewed by: Mgs. Marcela González Robalino English Professor c.c. 0603017708